Case report: Polymorphous low-grade neuroepithelial tumor of the young and supratentorial ependymoma diagnosed in an adult male - Xu, Cynthia Y.; Beers, Craig A.; Lu, Jian-Qiang; Hann, Crystal L.; Ramos, Ronald C. (Frontiers in Neurology, 2024)
Polymorphous low-grade neuroepithelial tumor of the young (PLNTY) is a rare central nervous system (CNS) pathology predominantly observed in the pediatric population. Ependymomas also exhibit a peak incidence in early childhood, with rare presentations after early adulthood. In this report, we describe a rare case of a 41-year-old man diagnosed sequentially with a polymorphous low-grade neuroepithelial tumor of the young, followed by a supratentorial ependymoma within a year. He underwent tumor resection for both tumors, as well as adjuvant radiation therapy for the ependymoma. Despite these interventions, he ultimately succumbed to tumor progression and postoperative complications. Currently, no genetic syndromes are known to link these two primary CNS tumors. Two commonalities at the chromosomal and cellular level include histone gene H3F3A mutations and positive glial fibrillary acidic protein staining on immunohistochemistry. To the best of our knowledge, this unique dual pathology has not been previously described in the literature, making this case an avenue for further investigation and research into connections between these two distinct CNS pathologies.